The Extent of The Application of The University of Science and Technology of Total Quality Standards in Accordance with The European Foundation Quality Management (EFQM) in The Strategic Planning - Riyadh Yahya Alghaili; Abdullah Ahmad Alshuraimi (University of Science and Technology, Yemen, 2016)
AbstractThis study aims to investigate the range of the application of total quality standards in accordance with the European Foundation Quality Management (EFQM) in the strategic planning of the University of Science and Technology (UST), Yemen, by answering the main question:- To what extent the total quality standards that are based on the EFQM are applied in the strategic planning from the viewpoint of UST senior management and medium management? In order to achieve the objectives of the study, the researchers adopted the descriptive analytical method by using the case study. the researchers reached the following findings:         1-        The findings showed that the senior management at the university has a role in the process of planning as the respondents agreed with the rate (%74.7). This role represented in some aspects such as formation of work teams for planning, training, and participating in some of their works.         2-        The findings also showed that there is a limited participation of staff in the process of strategic planning at UST as the respondents agreed with the rate (%63.3).         3-        The findings showed that there is acceptable application for some modern methods that are used to determine the customer's needs during the process of strategic planning at UST. The respondents agreed with rate (%63.0).         4-        The findings investigated that there is acceptable dependence on accurate information in the strategic planning at UST. The respondents agreed with the rate (%67.9).         5-        The findings illustrated that there is a lack in disseminating the strategy for all staff at UST as the respondents agreed with the rate (%59.2).   The findings generally show that there is a clear weakness in the application of total quality standards based on the EFQM during the planning process.